2017
DOI: 10.1111/hae.13180
|View full text |Cite
|
Sign up to set email alerts
|

Low agreement between fresh and frozen‐thawed platelet‐rich plasma in the calibrated automated thrombogram assay

Abstract: Fresh and ft-PRP cannot be assumed to show equal results in the TGA-CAT assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…The supernatant (platelet-poor plasma) was collected and all platelet pellets were frozen at − 80 °C. Although differences have been observed in fresh versus frozen PRP [28], due to logistical concerns and because freezing has been demonstrated to be a valid method to induce the release of growth factors [20], frozen PL was used in this experiment in place of the fresh PRP used in the field.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant (platelet-poor plasma) was collected and all platelet pellets were frozen at − 80 °C. Although differences have been observed in fresh versus frozen PRP [28], due to logistical concerns and because freezing has been demonstrated to be a valid method to induce the release of growth factors [20], frozen PL was used in this experiment in place of the fresh PRP used in the field.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas TG results in frozen-thawed PRP were significantly higher compared to fresh PRP obtained from the same healthy subjects, several features including the detection of activated protein C resistance were comparable for the two sample conditions [55]. Recent work including healthy subjects and individuals at risk for bleeding showed poor agreement between TG results from fresh and frozen-thawed PRP [56]. Whether TG variations depend on individual functional characteristics of platelets that differ with the underlying pathophysiological conditions is not yet understood.…”
Section: Uncertainties and Limitations Of Thrombin Generation In The mentioning
confidence: 96%
“…A few groups have compared some of the TG assays in the past, and concluded that there was a poor correlation between the assays. 19,20 It is accepted that part of the poor correlation is due to lack of standardization.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the Innovance ETP assay (Siemens Healthcare Diagnostics), HaemoScan Thrombin Generation Assay (HemoScan), and Pefakit TDT (Pentapharm) are performed using a chromogenic substrate. A few groups have compared some of the TG assays in the past, and concluded that there was a poor correlation between the assays 19,20 . It is accepted that part of the poor correlation is due to lack of standardization.…”
Section: Introductionmentioning
confidence: 99%